Compatibility of Clinical Manifestation with Skin Prick Test Result and Food Provocation Test in Food Cross Reaction - Azwin Lubis; Wisnu Barlianto; Anang Endaryanto; Ariyanto Harsono (Faculty of Medicine, Universitas Airlangga, 2017)
Background: Subjective diagnostic test of food allergy is hugely biased, resulting in irrational diet avoidance. Additional objective tools by skin prick test following food provocation test resulting more accurate cause and prevalence on population. Purpose: To evaluate the compatibility of clinical symptoms with skin prick test and provocation test for imunoglobulin E (IgE) mediated food allergy in Dr. Soetomo Hospital Surabaya. Methods: Cross sectional observational analytic study. Patient with allergy symptoms, diagnosed with food skin prick test followed by food provocation test. McNemar test and Kappa were used to analyze compatibility of skin prick test with food provocation test. Sensitivity and spesificity test of skin prick test toward food provocation test were done. Results: McNemar test between skin prick test and food provocation test are valued p<0.05 in all food allergen, except fruit p=0.607, but all Kappa test are low p<0.6. Fruit and chocolate showed low sensitivity (0.307;0.409) but with high spesificity (0.823;0.8333); egg and shrimp showed high sensitivity (0.777;1.000) but low spesificity (0.548;0.352); cow’s milk, seafish, and chicken meat showed sensitivity (0.636;1.000;0.785) and high specifity (0.607;0.625;0.631); fresh water fish showed low sensitivity and spesificity (0.500;0.583). IgE mediated symptoms profile is dominated by cough except for shrimp, and non-IgE mediated also is dominated by cough except seafish and shrimp. Conclusion: There is incompatibilty between result of skin prick test and food provocation test in IgE mediated food allergy. IgE mediated and non-mediated food allergy symptoms are dominated by airway, gastrointestinal tract, and skin symptoms. Food allergy symptoms are more related to IgE mediated than non-IgE mediated.